The Influence of Taxation Knowledge, Taxpayer Awareness, and Tax Sanctions on Individual Taxpayer Compliance (At the Bandung Cicadas Primary Tax Office) - Dela Adhanissa Alamsyah; Astrin Kusumawardani; Fransisko Caserio Daur (Komunitas Dosen Indonesia, 2024)
This research uses data from KPP Pratama Bandung Cicadas to highlight concerns about taxpayer compliance, especially with regard to self-assessed taxes. When it comes to tax knowledge, awareness, penalties and compliance, researchers have different opinions. The results highlight the influence of understanding, awareness, and impact on taxpayer behaviour as well as the collection of government taxes. An analysis of the relationship between taxpayer compliance and tax knowledge, awareness, and penalties is carried out through the use of descriptive and verification techniques in a quantitative research. Taxpayers of KPP Pratama Bandung Cicadas will be surveyed to determine the extent to which tax knowledge, awareness, and penalties influence compliance. This is done without comparing or linking the factors. Slovin was used to extract 100 taxpayers from a total of 300,740. We use quantitative and descriptive statistics. Tax compliance and tax policy should be improved as a result of this study. According to the research, people who are more aware of the tax rules are better able to pay their taxes. Enforcing tax rules through the use of tax penalties increases taxpayer understanding. According to the results of the research, the increase in taxpayer compliance at the Bandung Cicadas Primary Tax Service Office can be attributed to increased tax knowledge, awareness, and penalties. Given that these three factors statistically influence taxpayer compliance, it is important to study them together. Tax education, taxpayer awareness, and the effectiveness of tax penalties are some of the recommendations made in the study to increase taxpayer compliance.